Basal Settings Control Fast Ice Flow in the Recovery/Slessor/Bailey Region, East Antarctica - Diez, Anja; Matsuoka, Kenichi; Ferraccioli, Fausto; Jordan, Tom A; Corr, Hugh F; Kohler, Jack; Olesen, Arne V; Forsberg, René (Geophysical Research Letters, 2018)
The region of Recovery Glacier, Slessor Glacier, and Bailey Ice Stream, East Antarctica, has remained poorly explored, despite representing the largest potential contributor to future global sea level rise on a centennial to millennial time scale. Here we use new airborne radar data to improve knowledge about the bed topography and investigate controls of fast ice flow. Recovery Glacier is underlain by an 800 km long trough. Its fast flow is controlled by subglacial water in its upstream and topography in its downstream region. Fast flow of Slessor Glacier is controlled by the presence of subglacial water on a rough crystalline bed. Past ice flow of adjacent Recovery and Slessor Glaciers was likely connected via the newly discovered Recovery-Slessor Gate. Changes in direction and speed of past fast flow likely occurred for upstream parts of Recovery Glacier and between Slessor Glacier and Bailey Ice Stream. Similar changes could also reoccur here in the future.
Keywords: Antarktis; geofysikk; geologi; glasiologi; havnivåstigning; isbre; isstrøm

Topographic Steering of Enhanced Ice Flow at the Bottleneck Between East and West Antarctica - Winter, Kate; Ross, Neil; Ferraccioli, Fausto; Jordan, Tom A; Corr, Hugh F J; Forsberg, René; Matsuoka, Kenichi; Olesen, Arne V; Casal, Tania G (Geophysical Research Letters, 2018)
Hypothesized drawdown of the East Antarctic Ice Sheet through the “bottleneck” zone between East and West Antarctica would have significant impacts for a large proportion of the Antarctic Ice Sheet. Earth observation satellite orbits and a sparseness of radio echo sounding data have restricted investigations of basal boundary controls on ice flow in this region until now. New airborne radio echo sounding surveys reveal complex topography of high relief beneath the southernmost Weddell/Ross ice divide, with three subglacial troughs connecting interior Antarctica to the Foundation and Patuxent Ice Streams and Siple Coast ice streams. These troughs route enhanced ice flow through the interior of Antarctica but limit potential drawdown of the East Antarctic Ice Sheet through the bottleneck zone. In a thinning or retreating scenario, these topographically controlled corridors of enhanced flow could however drive ice divide migration and increase mass discharge from interior West Antarctica to the Southern Ocean.
Keywords: Antarktis; glasiologi; innlandsis; isgjennomtrengende; isstrøm; radarundersøkelser

A New Bathymetry for the Southeastern Filchner-Ronne Ice Shelf: Implications for Modern Oceanographic Processes and Glacial History - Rosier, Sebastian H R; Hofstede, Coen; Brisbourne, Alex Mark; Hattermann, Tore; Nicholls, Keith William; Davis, Peter E D; Anker, Paul; Hillenbrand, Claus-Dieter; Smith, Andrew M; Corr, Hugh F (Journal of Geophysical Research: Oceans, 2018)
The Filchner-Ronne Ice Shelf, the ocean cavity beneath it, and the Weddell Sea that bounds it, form an important part of the global climate system by modulating ice discharge from the Antarctic Ice Sheet and producing cold dense water masses that feed the global thermohaline circulation. A prerequisite for modeling the ice sheet and oceanographic processes within the cavity is an accurate knowledge of the sub-ice sheet bedrock elevation, but beneath the ice shelf where airborne radar cannot penetrate, bathymetric data are sparse. This paper presents new seismic point measurements of cavity geometry from a particularly poorly sampled region south of Berkner Island that connects the Filchner and Ronne ice shelves. An updated bathymetric grid formed by combining the new data with existing data sets reveals several new features. In particular, a sill running between Berkner Island and the mainland could alter ocean circulation within the cavity and change our understanding of paleo-ice stream flow in the region. Also revealed are deep troughs near the grounding lines of Foundation and Support Force ice streams, which provide access for seawater with melting potential. Running an ocean tidal model with the new bathymetry reveals large differences in tidal current velocities, both within the new gridded region and further afield, potentially affecting sub-ice shelf melt rates.
Keywords: Sørishavet; batymetri; brehylle; innlandsis; isbrem; isshelf; klima; oseanografi; tidevann